Diagnostic accuracy of functional magnetic resonance imaging, Wada test, magnetoencephalography, and functional transcranial Doppler sonography for memory and language outcome after epilepsy surgery: A systematic review. (30th October 2018) - Schmid, Elisabeth; Thomschewski, Aljoscha; Taylor, Alexandra; Zimmermann, Georg; Kirschner, Margarita; Kobulashvili, Teia; Brigo, Francesco; Rados, Matea; Helmstaedter, Christoph; Braun, Kees; Trinka, Eugen; ,
Summary: Objective: The European Union–funded E‐PILEPSY project was launched to develop guidelines and recommendations for epilepsy surgery. In this systematic review, we aimed to assess the diagnostic accuracy of functional magnetic resonance imaging (fMRI), Wada test, magnetoencephalography (MEG), and functional transcranial Doppler sonography (fTCD) for memory and language decline after surgery. Methods: The literature search was conducted using PubMed, Embase, and CENTRAL. The diagnostic accuracy was expressed in terms of sensitivity and specificity for postoperative language or memory decline, as determined by pre‐ and postoperative neuropsychological assessments. If two or more estimates of sensitivity or specificity were extracted from a study, two meta‐analyses were conducted, using the maximum ("best case") and the minimum ("worst case") of the extracted estimates, respectively. Results: Twenty‐eight papers were eligible for data extraction and further analysis. All tests for heterogeneity were highly significant, indicating large between‐study variability ( P < 0.001). For memory outcomes, meta‐analyses were conducted for Wada tests (n = 17) using both memory and language laterality quotients. In the best case, meta‐analyses yielded a sensitivity estimate of 0.79 (95% confidence interval [CI] = 0.67‐0.92) and a specificity estimate of 0.65 (95% CI = 0.47‐0.83). For the worst case, meta‐analyses yielded a sensitivity estimate of 0.65 (95% CI = 0.48‐0.82) and a specificity estimate of 0.46 (95% CI = 0.28‐0.65). The overall quality of evidence, which was assessed using Grading of Recommendations Assessment, Development, and Evaluation methodology, was rated as very low. Meta‐analyses concerning diagnostic accuracy of fMRI, fTCD, and MEG were not feasible due to small numbers of studies (fMRI, n = 4; fTCD, n = 1; MEG, n = 0). This also applied to studies concerning language outcomes (Wada test, n = 6; fMRI, n = 2; fTCD, n = 1; MEG, n = 0). Significance: Meta‐analyses could only be conducted in a few subgroups for the Wada test with low‐quality evidence. Thus, more evidence from high‐quality studies and improved data reporting are required. Moreover, the large between‐study heterogeneity underlines the necessity for more homogeneous and thus comparable studies in future research.